2020
DOI: 10.1099/mgen.0.000468
|View full text |Cite
|
Sign up to set email alerts
|

Long inverted repeats around the chromosome replication terminus in the model strain Bacillus thuringiensis serovar israelensis BGSC 4Q7

Abstract: Bacillus thuringiensis serovar israelensis is the most widely used natural biopesticide against mosquito larvae worldwide. Its lineage has been actively studied and a plasmid-free strain, B . thuringiensis serovar israelensis BGSC 4Q7 (4Q7), has been produced. Previous sequencing of the genome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…3 ), including repA , which indicated that pBtic235 genome replication can initiate without RepA. We detected multiple reads that connected the ends of the deleted region, showing that like the wild-type pBtic235 genome, the mutant pBtic235 genome was also circular 19 . Next, we purified the pBtic235 virions from the MMC-induced culture of GBJ002 and visualized their morphology using transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…3 ), including repA , which indicated that pBtic235 genome replication can initiate without RepA. We detected multiple reads that connected the ends of the deleted region, showing that like the wild-type pBtic235 genome, the mutant pBtic235 genome was also circular 19 . Next, we purified the pBtic235 virions from the MMC-induced culture of GBJ002 and visualized their morphology using transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 90%
“…GIL01 establishes a lysogenic cycle in the infected B. thuringiensis serovar israelensis strain GBJ002, a 4Q7 derivative cured of all plasmids and three chromosomal prophages, except for the pBtic235 prophage (Supplementary Fig. 1 ) 19 . Our aim was to to study transcription in strain GBJ002 in presence of GIL01.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation